PERLINDUNGAN HUKUM BAGI PENYANDANG DISABILITAS DI PT APPAREL ONE INDONESIA 1 - Hapsari, Herning Tyas Setyo; Saputra, Arikha (Universitas Muhammadiyah Ponorogo, 2023)
Workers with Disabilities, especially those working in private companies, have rights and obligations to obtain welfare. Private companies have an obligation to employ persons with disabilities as much as 1% (one percent) of the total number of employees working in the company. As explained in Article 53 paragraph (2) of Law Number 8 of 2016 concerning Persons with Disabilities which contains